Parental Roles in Supporting Vocabulary Learning Through YouTube Kids - Layla Shofiana, Khelin; Hapsari, Christianti Tri (English Education: Jurnal Tadris Bahasa Inggris, 2026)
This study investigates the roles of parents in supporting young learners' English vocabulary learning through YouTube Kids in home-based EFL settings. Using a qualitative descriptive design, data were collected through semi-structured interviews with eight purposively selected parents and analyzed using Braun and Clarke's thematic analysis. The findings revealed four interconnected themes: parents as learning facilitators, language mediators, digital supervisors, and individuals who navigate various challenges in supporting children's vocabulary learning. Parents actively selected educational content, explained unfamiliar vocabulary, encouraged vocabulary practice, supervised children's digital media use, and created supportive home learning environments. Although parents encountered challenges, including limited time, children's digital distractions, and limited English proficiency, they continuously adapted their mediation practices to support children's learning. The findings demonstrate that the educational value of YouTube Kids depends not only on the availability of digital content but also on purposeful parental mediation. This study contributes to the growing literature on technology-assisted language learning by providing a deeper understanding of parental mediation practices in home-based EFL contexts and offering practical insights for parents, educators, and educational content developers.